In silico Investigation and Molecular Docking Study of Triazolo-thiadiazole Derivatives for Antimicrobial, Anti-inflammatory and Anti-diabetic Activity - Dighe, Amol Sopanrao; Sen, Ashim Kumar (Indian Journal of Pharmaceutical Education and Research, 2021)
Triazolo-thiadiazole and connected fused ring in heterocyclic compounds are of highly interest in potential bioactive molecules. Triazolo-thiadiazole derivatives have lead of organic chemists due to their good biological and chemotherapeutic significance. Research in the field of anti-mycobacterium, anti-inflammatory, anti-diabetic and anti-microbial therapies are ongoing and studies are seeking. Therefore, the discovery of new effective anti-mycobacterium, anti-inflammatory, anti-diabetic and antimicrobial agents are imperative. Swiss programs are used to predict Triazolo-thiadiazole derivatives properties that are important for drug profile. Later, all of them were docked into the active sites of enzymes namely Ribosomal RNA large subunit methyltransferase (1P91), PeriplasmicOligopeptide-Binding Protein (1B05) and Protein-tyrosine phosphatase, non-receptor type 1 (1q6s), those were considered in Antidiabetic studies of triazolo-thiazazole derivative. Docking study when compared with Triazolo-thiadiazole derivatives with standard drug, derivative docking result is better. Ciprofloxacin, ibuprofen, and acarbose have been used as standard drugs for antimicrobial, anti-inflammatory and anti-diabetic activity in comparative docking studies.
Keywords: Triazolo-thiodizole; Antibacterial; Anti-diabetic; Antitubercular; Anti-inflammatory